Preparation of water‐compatible antifungal polyurethane with grafted benzimidazole as the antifungal agent. Issue 14 (22nd November 2014) - Chung, Yong‐Chan; Kim, Ha Youn; Choi, Jae Won; Chun, Byoung Chul
ABSTRACT We compared two series of benzimidazole (BI)‐grafted polyurethane (PU), one of which was water‐compatible, to compare their antifungal activities. The water‐compatible PU series had an additional 2, 2‐bis(hydroxymethyl)propanoic acid group in the PU backbone. The water‐compatible PU series had a lower crosslinking density and tensile strength compared to the other PU series with increasing BI content. Although ordinary PU did not suppress fungal growth (Chaetomium globosum), the water‐compatible PU completely suppressed the growth even though it contained half as many BI groups. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41676.